Dynamic-SERS optophysiology: a nanosensor for monitoring cell secretion events - Lussier, Félix; Brulé, Thibault; Vishwakarma, Medhavi; Das, Tamal; Spatz, Joachim P.; Masson, Jean-François (Nano letters, 2016)
We monitored metabolite secretion near living cells using a plasmonic nanosensor. The nanosensor created from borosilicate nanopipettes analogous to the patch clamp was decorated with Au nanoparticles and served as a surface-enhanced Raman scattering (SERS) substrate with addressable location. With this nanosensor, we acquired SERS locally near Madin-Darby canine kidney (MDCKII) epithelial cells, and we detected multiple metabolites, such as pyruvate, lactate, ATP, and urea simultaneously. These plasmonic nanosensors were capable of monitoring metabolites in the extracellular medium with enough sensitivity to detect an increase in metabolite concentration following the lyses of MDCKII cells with a nonionic surfactant. The plasmonic nanosensors also allowed a relative quantification of a chemical gradient for a metabolite near cells, as demonstrated with a decrease in relative lactate to pyruvate concentration further away from the MDCKII cells. This SERS optophysiology technique for the sensitive and nondestructive monitoring of extracellular metabolites near living cells is broadly applicable to different cellular and tissue models and should therefore provide a powerful tool for cellular studies.
Gesehen am 20.05.2020